Genome size variation in guayule and mariola: fundamental descriptors for genomics-assisted breeding of polyploid plant taxa - Sanchez, Paul L.; Costich, Denise E.; Friebe, Bernd R.; Coffelt, Terry A.; Jenks, Matthew A.; Gore, Michael A. (My University, 2014)
Guayule (Parthenium argentatum A. Gray) has tremendous potential as a domestic source of natural rubber production in the southwestern United States. However, genetic improvement of guayule has been slowed by its complex mode of reproduction, natural ploidy series, and lack of genetic and genomic resources. The interspecific hybridization of guayule with its closest sister taxon mariola (P. incanum Kunth) offers an opportunity to access novel genetic variation for guayule breeding programs, but mariola accessions available from the U.S. National Plant Germplasm System (NPGS) have never been evaluated for natural variation in ploidy level. In addition, the nuclear genome sizes for guayule and mariola at any ploidy level are unknown. To that end, we examined the ploidy of 10 mariola accessions, which revealed a natural polyploid series ranging from triploid (2n = 3x = 54) to pentaploid (2n = 5x = 90). In contrast, a ploidy analysis of five guayule accessions uncovered a natural polyploid series that ranged from diploid (2n = 2x = 36) to hexaploid (2n = 6x = 108). More than one ploidy level among individual plants (mixed ploidy) and instances of aneuploid plants were observed for accessions of both guayule and mariola. The nuclear genome sizes of guayule and mariola were similar at identical ploidy levels, and the genome size of diploid guayule (1624 Mb) was almost twofold smaller than the genomes of sunflower (H. annuus L. 2n = 2x = 34) and lettuce (L. sativa L.; 2n = 2x = 18), two other Compositae (Asteraceae) species that are being genome-sequenced. The results from this study will serve as a foundation for interspecific breeding and genome sequencing of guayule and mariola.
Genome size variation in guayule and mariola: fundamental descriptors for polyploid plant taxa
Citation: Sanchez, P., . . . & Gore, M. (2013). Genome size variation in guayule and mariola: Fundamental descriptors for polyploid plant taxa. Industrial Crops and Products, 54(1), 1-5. https://doi.org/10.1016/j.indcrop.2013.12.052
Keywords: Guayule; Mariola; Ploidy level; Nuclear Genome size; Flow cytometry